2019
DOI: 10.21271/zjpas.31.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Dates and Varieties of Cotton (Gossypium hirsutum L.) on Growth and Yield Parameters.

Abstract: The sowing date trials comprised of three planting dates on three cotton varieties (Lachata, Stoneville 213 and Coker 310), were conducted to investigate appropriate sowing time of the varieties at Erbil, Kurdistan during 2017. It was also to investigate the effect of climate change of sowing time. Results indicated that sowing dates, varieties and interactions significantly affected all studied characteristics. The highest plant height was recorded of Stoneville 213 which was by (110.8) cm in April 27. Variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
4
6
0
Order By: Relevance
“…(Figure 8b). These results in accordance with Salih (2019) investigated that earliest rate of maturity influenced by variety. On the other hand, plastic mulch enhanced rate of maturity (72 %) as compared to no mulch (Dong et al, 2009).…”
Section: Effect Of Varieties Plant Spacing and Mulching On Earliness ...supporting
confidence: 91%
See 3 more Smart Citations
“…(Figure 8b). These results in accordance with Salih (2019) investigated that earliest rate of maturity influenced by variety. On the other hand, plastic mulch enhanced rate of maturity (72 %) as compared to no mulch (Dong et al, 2009).…”
Section: Effect Of Varieties Plant Spacing and Mulching On Earliness ...supporting
confidence: 91%
“…Maximum and minimum numbers of seeds boll -1 were 27.1 and 25.4, for V2 and V1, respectively (Figure 4a). These results supported by other researchers, such as varieties of cotton as well non-significantly influenced number of seeds boll -1 (Salih, 2019). Akbar et al (2015) found that plant spacing not influenced to number of seeds boll -1 ; plant spacing of (20 and 30) cm had (28.33 and 28.55) seeds boll -1 .…”
Section: Effect Of Varieties Plant Spacing and Mulching On Number Of ...supporting
confidence: 77%
See 2 more Smart Citations
“…Accordingly, flowering abortion would be expected to increase during drought stress as it decreases the flux of photosynthate supply from source leaves to the vegetative tissues. Also, drought stress may change the concentration of ABA in the plants, and thereby induce flower abortion in drought-stressed crops (Salih, 2019).…”
Section: Calyx Yieldmentioning
confidence: 99%